Donnie Darko [videorecording (DVD)] - Kelly, Richard, 1975-; Gyllenhaal, Jake, 1980-; Malone, Jena, 1984-; Barrymore, Drew; McDonnell, Mary; Ross, Katharine, 1940-; Swayze, Patrick; Wyle, Noah, 1971-; Poster, Steven, 1944- (20th Century Fox Home Entertainment, 2001)
In this psychological thriller, a troubled teen comes face to face with his destiny. As he struggles with suburban alienation and delusions, visitations from a demonic rabbit lead him through dark visions of the future.